Analysis for mangrove ecosystem management priority using Analysis Hierarchy Process (AHP) in Sorong City, West Papua, Indonesia - Tabalessy, Roger R; Wantasen, Adnan S; Schaduw, Joshian N.W. (Graduate Program of Sam Ratulangi University, 2013)
Indonesiaâ€™s mangrove forest is decreasing. Factors affecting this condition are excessive utilization for livelihood and market demand without considering its sustainability for the future. As a result, mangrove forest degrades year by year. The present study aimed to analyse which stakeholder is the priority for mangrove ecosystem management in the city of Sorong, West Papua, Indonesia, and which factors are the priority for sustainable management. Primary data were collected using questionnaire with interview technique and were analysed using Expert Choice 11 software. The result showed that local government was the stakeholder possessing major priority in management which was supported by others (community and NGO), and the ecological factor was the priority in management, while the economic, social, and institutionalfactors were the supporting factors for sustainability.Â Luas hutan mangrove di Indonesia sedang mengalami penurunan. Faktor yang mempengaruhi kondisi ini, yaitu pemanfaatannya secara berlebihan untuk memenuhi kebutuhanan hidup maupun permintaan pasar tanpa mempertimbangkan keberlanjutannya di masa depan. Sebagai akibatnya tutupan hutan mangrove semakin berkurang dari tahun ke tahun. Penelitian ini bertujuan menganalisis stakeholder manakah yang menjadi prioritas dalam pengelolaan ekosistem mangrove di Kota Sorong, Papua Barat, Indonesia, dan faktor manakah yang menjadi prioritas dalam pengelolaan secara berkelanjutan. Data primer dikumpulkan menggunakan angket dengan teknik wawancara, dan kemudian dianalisis menggunakan software Expert Choice 11. Hasil penelitian menunjukkan bahwa stakeholder Pemda merupakan prioritas utama dalam pengelolaan ekosistem mangrove dan ditopang oleh stakeholder lainnya (Masyarakat dan LSM), dan faktor prioritas dalam pengelolaan adalah ekologi, sedangkan faktor ekonomi, sosial, dan kelembagaan merupakan faktor pendukung untuk terciptanya pengelolaan ekosistem mangrove yang berkelanjutan.